Leapfrogging into the unknown: The future of structural change in the developing world - Lukas Schlogl (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper traces a set of major trends and future scenarios in global structural change. It argues that across multiple domains of change, developing economies are facing novel constellations of lateness and prematurity in technological and economic development. The paper explores these novel constellations in employment and value added, global trade, and technological upgrading. It argues that an expansion of service sector work in lockstep with rising economic development will likely continue to shape the medium-term future of structural transformation, albeit with trends of convergence and a hybridization of sectors. New employment challenges may be emerging for participants in a global value chain due to the debated threat of 'reshoring' of offshored production. The paper finally discusses automation in the non-tradable sector and the ramifications of technological leapfrogging or 'technology creep' for the future of structural change.
Keywords: O14; O20; O33; 330; Entwicklungsländer; Developing countries; Dienstleistungssektor/Tertiärer Sektor; Service/tertiary sector